2008
DOI: 10.1007/s11661-008-9514-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact Response and Microstructural Evolution of Biomedical Titanium Alloy under Various Temperatures

Abstract: A compressive split-Hopkinson pressure bar and transmission electron microscope (TEM) are used to investigate the mechanical behavior and microstructural evolution of biomedical Ti alloy deformed at strain rates ranging from 8 · 10 2 s -1 to 8 · 10 3 s -1 at temperatures between 25°C and 900°C. In general, the results indicate that the mechanical behavior and microstructural evolution of the alloy are highly sensitive to both the strain rate and the temperature conditions. The flow-stress curves are found to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 33 publications
2
21
2
Order By: Relevance
“…In equation (5), stresses ı 1 and ı 2 are obtained from tests conducted at temperatures of ଵ and ଶ , respectively. For Ti6554, the strain rate sensitivity decreases with increasing temperature as shown in Fig.4a, which is also observed for most other metals [20,21,[32][33][34]. The temperature sensitivity of Ti6554 increases with increasing temperature.…”
Section: Dynamic Stress-strain Responsesupporting
confidence: 74%
See 2 more Smart Citations
“…In equation (5), stresses ı 1 and ı 2 are obtained from tests conducted at temperatures of ଵ and ଶ , respectively. For Ti6554, the strain rate sensitivity decreases with increasing temperature as shown in Fig.4a, which is also observed for most other metals [20,21,[32][33][34]. The temperature sensitivity of Ti6554 increases with increasing temperature.…”
Section: Dynamic Stress-strain Responsesupporting
confidence: 74%
“…This indicates that shear bands tend to form at higher strain rates. It has been reported that high strain rates and low temperatures are beneficial for the formation of shear bands in titanium alloys [20]. However, in this study it was observed that the adiabatic shear bands prefer to form at higher temperatures.…”
Section: Novel į Precipitate Morphologies and Strain Localizationcontrasting
confidence: 59%
See 1 more Smart Citation
“…As to temperature sensitivity, there exist some contradictions. In Refs [85,118,121,129], the temperature sensitivity of the investigated metals was interpreted to increase with increasing strain, strain rate and…”
Section: Strain Rate Sensitivity and Temperature Sensitivitymentioning
confidence: 99%
“…As to temperature sensitivity, there exist some contradictions. In Refs [85,118,121,129], the temperature sensitivity of the investigated metals was interpreted to increase with increasing strain, strain rate andHongyi Zhan have conducted dynamic compressive tests on the β Ti-Nb-Zr-Mo-Sn alloy and found that the flow stress decreased slightly when the strain rate was raised to 1000 s -1 as shown in Fig.14. It may be attributed to the fact that high strain rates increased the volume fraction of α" martensitic phase which has a lower hardness than β phase.…”
mentioning
confidence: 99%